Peran Emotional Connections: Parental Strategies for Building Attachment in 4-5 Year Old Children - Ponirah, Ponirah; Yulianty S, Nadya; Syahidin, Samin (Muttaqien Publishing, Pusat Penelitian dan Pengabdian kepada Masyarakat STAI DR.KH.EZ.Muttaqien Purwakarta, 2024)
Abstract: This study aims to describe and how the role of parents in building attachment (attachment) in children aged 4-5 years. This is important to examine considering how far the role of parents to early childhood attachment in social life where the development of attachment is strongly influenced by parental sensitivity in responding to children, whether the response is given as soon as possible when the child needs help or there is a delay in response and whether the response given is the right response or not. The method used in this study is qualitative with data collection techniques using triangulation techniques (observation, interviews and documentation) by taking a sample of parents and students as many as 3 people each as respondents.Based on the results of data analysis, it can be concluded that the role of parents that have been carried out in building attachment to children as a whole makes efforts including giving advice and habituation so that children feel comfortable in socializing without having to be accompanied by attached figures. Factors that affect attachment in children aged 4 – 5 years are: A child’s satisfaction with gifts from his parents, the action of reaction or response to any behavior that shows attention and frequent interaction with children, then the child will give attachment to his parents Keywords: Attachment, Parental Strategies